THE INFLUENCE OF THE SALINITY TOWARDS THE GROWTH OF SPIRULINA PLATENSIS CULTIVATION OF BIOMASSSA MIKROALGA ON THE SCALE SEMI OUTDOOR - Merry Sintya Dewi; Joko Samiaji; Irvina Nurrachmi (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
ABSTRACT Mikroalga is a large group of aquatic organisms that is very diverse, does not have a complex cell structure, with a diameter between 1-50 µm and can be found in various environments such as freshwater, brackish and sea water or damp places other mikroalga which formed the basis of the food chain. This research was carried out from December-January 2018 in the laboratory of Marine Biotechnology and Marine Chemistry Laboratory, Faculty of Fisheries and Marine Science University of Riau. The aims is to find out the influence of biomass and growth rate differences salinity (ppt, 15 20 25 ppt, ppt and 30 ppt) against a platensis cultivation mikroalga s. on the scale of the spring pool. The method used is the method of experiment using Random Design. The results showed that the growth of biomass at all salinity treatments experienced the highest increase on day 10 observations. The number of maximum biomass growth was 0.078 g/L salinity treatment at 25 ppt, and growth the lowest biomass is 0.019 g/L on the treatment of 30 ppt. Statistical analysis (ANOVA) showed that the difference in salinity towards the growth of biomass mikroalga s. platensis gained real influence there, where values (P < 0.005). Linear regression analysis shows that the influence of salinity towards the growth of the biomass is weak, with the value of the coefficient of determination R2 = 0.012 and coefficient of correlation r = 0.109. Keywords: Mikroalga,Spirulinaplatensis, Biomassgrowth, Salinity